Building Assessment Toolkit to Assess Collaborative Problem Solving Competence through Teaching Chemistry of the Non-Metals - Lien, Vu Phuong; Vy, Nguyen Thi Phuong; Loan, Phan Thi Quynh (VNU Journal of Science: Education Research, 2019)
This article presents the structure of student’s collaborative problem solving competence using theoretical research. Based on the results published by Patrick's team in 2014, 2015 and OECD 2015, this article proposes 4 assessment levels corresponding to each specific criterion of three component competencies: (1) establishing and maintaining shared understanding; (2) taking appropriate action to solve the problem; and (3) establishing and maintaining a team organization. The paper also proposes a matrix of assessment toolkits and corresponding criteria of collaborative problem solving competence in teaching chemistry of the non-metals using interdisciplinary integrated teaching perspective and Kolb's Experiential Learning Cycle. Each assessment tool specifically analyzes the functions and techniques implemented in students' collaborative problem solving processes.